Intra-cranial Chondroma: A Case Report and Problematic Diagnosis - Arezoo Eftekhar Javadi; Elham Nazar; Hedieh Moradi Tabriz (Iranian Society of Pathology, 2020)
Introduction: Chondroma is a benign cartilaginous tumor. It is found very rarely in the head and neck. Case presentation: This report describes a 25-year-old woman who presented with generalized headache from 4 months ago. The patient underwent excisional surgery. The histological examinations revealed benign cartilage forming tumor, compatible with chondroma. The radiologic and histologic correlation confirmed the diagnosis. Based on the diagnosis, the patient received no more treatment. Conclusion: We concluded that intracranial chondroma should be included in the differential diagnosis of a calcified mass on skull imaging. Proper diagnosis is necessary for further patient management.